Preemptive Versus Reactive Topical Clobetasol for Regorafenib-Induced Hand-Foot Reactions: A Preplanned Analysis of the ReDOS Trial. (6th March 2021) - Jatoi, Aminah; Ou, Fang-Shu; Ahn, Daniel H.; Zemla, Tyler J.; Le-Rademacher, Jennifer G.; Boland, Patrick; Ciombor, Kristen K.; Jacobs, Nisha L.; Pasche, Boris; Cleary, James M.; McCune, Jeannine S.; Pedersen, Katrina S.; et al.
Abstract: Background: Hand-foot skin reaction (HFSR) is the most common regorafenib-induced adverse event and is in need of effective prevention and palliation. Materials and Methods: The Regorafenib Dose Optimization Study (ReDOS), a four-arm, previously published trial with a 1:1:1:1 randomization scheme, was analyzed in a manner in keeping with the original protocol to assess whether clobetasol 0.05% cream (a corticosteroid) applied to the palms and soles twice per day for 8 weeks was more effective when prescribed preemptively (before the development of HFSR) versus reactively (after the development of HFSR). Patients were assessed during the first two cycles of regorafenib. Results: Sixty-one patients received preemptive clobetasol, and 55 received reactive clobetasol. Groups were balanced on demographics. Over the first two cycles, no evidence of HFSR occurred in 30% with preemptive clobetasol versus 13% with reactive clobetasol ( p = .03). During the first cycle, 54% and 45% of patients had no HFSR with preemptive and reactive clobetasol, respectively ( p = .35). During the second cycle, 33% and 15% had no HFSR with preemptive and reactive clobetasol, respectively ( p = .02). During the second cycle, rates of grade 1, 2, and 3 HFSR were 30%, 8%, and 3%, respectively, with preemptive clobetasol and 43%, 18%, and 7%, respectively, with reactive clobetasol ( p = .12). Patient-reported outcomes showed HFSR compromised nearly all activities of daily living with worse quality of life in patients who received reactive versus preemptive clobetasol. No clobetasol-induced adverse events were reported. Conclusion: Preemptive clobetasol might lessen regorafenib-induced hand-foot reactions compared with reactive therapy. Further confirmatory studies are needed in a larger patient cohort. Implications for Practice: Regorafenib causes hand-foot skin reactions. Preemptive clobetasol, a high-potency topical corticosteroid, appears to lessen the severity of this adverse event. Although further study is needed, the favorable adverse event profile of this intervention might prompt clinicians to discuss this option with their patients. Abstract : Hand-foot skin reaction is a common regorafenib-induced adverse event. This article reports on the use of topical clobetasol and its role when administered preventively, before a skin reaction occurs.